Blue carbon dynamics and mangrove extent: a case study from the IndonesiaTimor Leste Coastal ecosystem - Wanri Sitanggang; Diah Permata Wijayanti; Rudhi Pribadi; Chrisna Adhi Suryono; Maria Dyah Ayu Pitaloka; Egidius Naitkakin; Daniel Candido Da Costa Soares; Herning Pramudya; Yosni Kiuk (Faculty of Marine and Fisheries, Universitas Syiah Kuala, 2025)
Around 20% of mangrove forests in Indonesia are in a degraded condition, which has a negative impact on the potential for blue carbon storage. When mangroves are damaged or degraded, carbon stored in the soil and vegetation can be released back into the atmosphere as CO2, ultimately increasing greenhouse gas emissions and exacerbating climate change. Mangrove forests can store up to four times more carbon per hectare, around 8001,200 tons per hectare, than terrestrial tropical forests. This research was conducted in the Wini mangrove forest area, North Central Timor, East Nusa Tenggara (NTT) which directly borders Timor Leste. The determination of the location of the observation station was based on a map of changes in mangrove forest land use obtained from the Geospatial Information Agency. The parameters measured included organic carbon, mangrove area and sediment type. Organic carbon was analyzed using the Loss on Ignition (LOI) method, and sediment grain size was measured using a particle size analyzer. The results of the study showed that the average organic carbon stock in mangrove forests reached 570,600843,600 tons per hectare, with an average change in the area of mangrove forests from 2013 to 2023 of 181.29 hectares and the type of sediment dominated by sandy mud. This change in area is caused by the conversion of mangrove land into ponds, rice fields, and settlements.Keywords:MangroveCarbonSedimentborder Area